Effect of the time factor on the hydraulic activity of mechanically activated saponin-containing powder - Marina V. Morozova; Maria A. Frolova (Нанотехнологии в строительстве, 2025)
Introduction. The article examines the problem of the development of transport infrastructure in the Solovetsky archipelago and proposes a solution to reduce the cost of manufacturing reinforced concrete slabs for the road surface. It is proposed to use saponite-containing waste (SCW) of the mining and processing plant JSC Severalmaz as a mineral additive in concrete. Studies have shown that mechanically activated saponite-containing powder (MSP) improves concrete performance and reduces binder consumption. The use of MSP makes it possible to solve the problem of waste disposal and reduce environmental damage. The purpose of the work is to assess the effect of the time factor on the hydraulic activity of the mechanically activated saponite containing powder, since the activity of the additive may change during long-term storage. It is known that the degree of activity of mineral components is usually estimated by the amount of Ca2+ ions absorbed from a saturated lime solution. A number of direct analytical methods are available to monitor the change in Ca(OH)2 content over time during the course of the hydraulic reac tion. This technique, based on the measurement of the potential of the ion-selective electrode, is fully suitable for monitoring the hydraulic activity of the MSP. Methods and Materials. Saponite-containing waste was used as the main material for the studies, which was isolated, dried and dispersed. A mechanically activated saponite-containing powder was thus obtained. Control of the degree of grinding of the obtained finely divided MSP samples was carried out according to the specific surface area (Ssp , m2/kg). To perform potentiometric analysis, an electrode system consisting of a measuring electrode with a calcium ion detection function (pCa) and a reference electrode was used. In preparation for the experiment, the calcium selective electrode of the Elite-041 model was kept for three days in a calcium chloride solution with a concentration of 0.01 mol/L. The electrode was then washed with distilled water and calibrated to solutions with concentrations (CCa ) of 10–1, 10–2, 10–3, 10–4 and 10–5 mol/L, for which pCa = 1÷5. To study the sorption capacity, a lime solution with a concentration of 0.015 mol/l was prepared, as well as a suspension from samples of fine mineral saponite-containing powder. A solution of lime with a volume of 0.2 ml was successively added to the resulting suspension by a doser, while measuring the electromotive force (potential) of the system with continuous stirring. Based on the obtained potential values (mV), the concentration of calcium ions (Сfact Ca) in the bulk phase of the suspension was calculated using С teor Ca and Сfact Ca, and the hydraulic activity coefficient a predetermined calibration relationship. Further, using the algorithm for calculating the activity parameters of powders, according to potentiometry data, the maximum amount of absorbed calcium hydroxide (∆ССaO ) was determined as the difference between the . Results and Discussion. The resulting mechanically activated saponite-containing powder had a specific surface area of 196 m2/kg (10 min), 644 m2/kg (30 min), 1209 m2/kg (60 min), 1428 m2/kg (90 min) at different milling times. The preliminary calibration dependence of the potential of the electrode pair on the pCa value is characterized by the linear equation: E = –23,23pCa+520,35. It was found that when adding a lime solution to the suspension, an increase in EMF is observed due to the sorption of calcium ions by a mechanically activated saponite-containing powder. After reaching the threshold volume of the Ca(OH)2 solution, the potential stabilizes. With a further increase in the concentration of calcium ions, when their interaction with the MSP particles ceases, the E value increases again. Further, dependencies were obtained for all batches of the experiment, the difference of which lies only in the quantitative characteristics of the functional parameters. Initial value of electrode pair potential characterizes background concentration of calcium ions determined by their residual content in water and/or MSP. The obtained functional relationships of the Сfact Ca = f(Сteor Ca) for the test samples made it possible to determine the threshold values of the concentration of calcium ions in the solution, the excess of which creates their excess in the reaction medium. The built functional dependence of the G∞ = f(Ssp ), showed that the G∞ reaches its maximum value already at a specific surface area of more than 600 m2/kg (30 minutes of grinding). Since the grinding of 10 minutes has little effect on the specific surface area of the saponite powder, which affects the value of the hydraulic activity coefficient of the MSP, the dependence of G∞ = f(Ssp ) for grinding more than 10 minutes was considered. Extrapolation of the dependence on the specific surface area of the powder to 300 m2/kg (obtained industrially) gives a value of G∞ = 0.772, which is 5% lower than the maximum value in the experiments. To study the effect of time on hydraulic activity, powder after 60 minutes grinding (Ssp = 1209 m2/kg) was used, assuming that a high specific surface area would enhance the change in storage reactivity. Experimental characteristics (electrode pair potential) were measured after 7, 14 and 30 days of exposure. The obtained results showed that during storage of mechanically activated saponite containing powder, its specific surface area decreases due to conglomeration of clay particles. The obtained data, in our opinion, state the fact that the hydraulic activity of mechanically activated saponite-containing powders remains quite high for a long time (30-day) in a wide range of variation of their specific surface area (300÷1200 m2/kg). Conclusion. It is shown that potentiometric method of determination of sorption capacity to calcium oxide is effective as express method for evaluation of hydraulic activity of mechanically activated saponite-containing powder and influence of time. At the same time hydraulic activity of mechanically activated powders is linearly related to specific surface (300÷1200 m²/kg), besides, nature of this connection is described by linear equation with high value of approximation reliability factor (0.99). MSP retain hydraulic activity during natural storage for 30 days with a decrease in hydraulic activity by 4.1%.